Reflections on Métissage as an Indigenous research praxis. (June 2019) - Burke, Susan; Robinson, Rheanna
This article explores the use of Métissage as an Indigenous research praxis. The authors, both Métis academics from the country now called Canada, discuss the individual journey they each took in using Métissage for their doctoral research studies. Both the possibilities and limitations inherent in this research framework are outlined. Although Métissage is described in the context of the Canadian Métis experience, recommendations are also given for how this theory can be used by both other Indigenous researchers and non-Indigenous researchers.